CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP PECAHAN - Rina Indriani; Ari Metalin Ika Puspita; Mimin Ninawati; Hany Handayani; Agusfianuddin Agusfianuddin (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
One of the basic abilities in learning mathematics is the ability of students to understand mathematics. Mathematical comprehension ability will develop other mathematical abilities, including communication, connection and problem-solving abilities. To be able to hone students 'mathematical abilities, a learning model is needed that is appropriate to the students' character and the material being taught. One learning model that can improve student learning outcomes is the Contextual Teaching and Learning (CTL) model. The method used in this study is Classroom Action Research (CAR). Subjects in this study were fifth grade in Elementary School. The instruments used in this study were tests and observation sheets of teacher and student activities. Based on the analysis of research data, it is concluded that CTL can improve the ability of mathematical understanding of fraction concept for elementary students. Thus, the use of CTL learning models can be used as an alternative learning to be applied to learning mathematics in elementary school especially on learning concept of fractions.